Growth Performance of Broiler Quails Fed with Enriched Probiotic Feed - Norshida, Ismail; Ahmad Syazni, Kamarudin; Raynu Su, Wan Nong; Nur Azri, Mohamad Arshad (2018)
Probiotic can help in stimulating the growth and development of immune organs, improve level of immunoglobulin and antibody as well as improve immune system in animal. This present study was carried out to determine the effect of feed enriched with probiotics on the growth performance and hepatosomatic index of broiler quails. A total of 240 quails were divided into four groups with three replicates per group. Each treatments group has a different feeding treatment in which treatment 1 (T0) act as control with no probiotic, treatment 2 (T1) with 0.05% probiotic, treatment 3 (T2) with 0.20 % probiotic added and treatment 4 (T3) with 0.35 % probiotic, respectively. Probiotic was mixed in feed of quails starting from day 14 until day 42 and quails were fed ad-libitum twice per day. Results showed that there were significant differences between treatment groups and control in weight gain (p<0.05), average daily gain (ADG), feed conversion ratio (FCR) and feed intake (FI). T2 showed the best growth performances among groups after day 42. There were no significant differences in hepatosomatic index between treatment group and control (p<0.05). This may suggest that different concentration of probiotic has no adverse effect on liver of quails. In conclusion, the study suggests that probiotic can improve growth performance with no adverse effect on the liver of the quails.